Strengthening benefit reserves from actuarial reserve liabiligy to pre-need reserves - Mancao, Vina Jassen B.
The Actuarial Reserve Liablity (ARL) is the measure of future obligations of a pre-need company to its policyholders. In an attempt to reduce the crises plaguing the industry, the Securities and Exchange Commission resolved to adopt the Pre-Need Re¬serves (PNR) as replacement to the ARL. The main diﬀerence between the ARL and the PNR is that the former uses pricing interest rate on the entire portfolio to calcu¬late reserves whereas the latter uses attainable interest rate for fully paid plans availing within ﬁve years, and uses pricing interest rate for the rest of the plans in the portfolio. This paper intends to show the impact of decreasing interest rates in determining pol¬icy reserves by obtaining the diﬀerence among reserves valued at several interest rates. Moreover, this paper aims to illustrate the gap between ARL and PNR as time passes, and the additional amount the company has to set up when the policies become within ﬁve years from date of maturity. We will discuss any other ﬁndings and/or observations, and recommend extra measures to be taken in setting up PNR so as to lessen the eﬀect of putting up additional reserves during the last ﬁve years before a policy reaches its maturity dat